Groundwater Quality In Arid Regions: The Case Of Hassi Messaoud Region (se Algeria) - Bouselsal, B. (University of Eloued جامعة الوادي, 2017)
After chemical quality study, it has been realized that the groundwater of Hassi Messaoud region isn’t drinking one according to WHO and Algerian standards for drinking water. This water is highly mineralized and very hard and its major concentrations are often higher than recommended standards, so it requires treatment before use. The time that irrigation water quality is based on riverside standards (1954), the waters of the terminal complex of aquifers have average SAR values high, these waters arrange themselves in the poor and bad classes. However Continental Intercalary waters arrange themselves in the poor classes for irrigation.
Article in Journal of Fundamental and Applied Sciences Vol 09, N 01
Keywords: Terminal Complex, continental intercalary, WHO, potable, Irrigation.